Pembagian Pembayaran Piutang Kreditur Menurut Azas Keadilan Dalam Hukum Kepailitan : (UU No 37 Tahun 2004 Tentang Kepailitan Dan (PKPU)) (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Bankruptcy is a business settlement process through litigation, namely through the commercial court. Bankruptcy is regulated in Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations or abbreviated as UUK 2004. Prior to the promulgation of UUK 2004, it was about Faillissement Verordening (Law on Bankruptcy) which was then updated through Government Regulation in Lieu of Law Number 1 of 1998 and then ratified as Law Number 4 of 1998. Based on the explanation in the background section of the problem, the problem is how to take legal action in bankruptcy cases according to Law Number How to distribute payments for creditors' receivables according to the principles of justice in bankruptcy law. In Article 16 paragraph (1) of Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations ("UU 37/2004") it is stated that the curator has the authority to carry out the duties of managing and/or settling bankrupt assets from the date the bankruptcy disclosure is made, even though against the decision, cassation or reconsideration is granted. What is meant by "settlement" is the cashing out of assets to pay or settle debts.